Biomarkers for the Detection of Prenatal Alcohol Exposure: A Review. (18th January 2017) - Bager, Heidi; Christensen, Lars Porskjær; Husby, Steffen; Bjerregaard, Lene
Abstract : Alcohol exposure during pregnancy can cause adverse effects to the fetus, because it interferes with fetal development, leading to later physical and mental impairment. The most common clinical tool to determine fetal alcohol exposure is maternal self‐reporting. However, a more objective and useful method is based on the use of biomarkers in biological specimens alone or in combination with maternal self‐reporting. This review reports on clinically relevant biomarkers for detection of prenatal alcohol exposure (PAE). A systematic search was performed to ensure a proper overview in existing literature. Studies were selected to give an overview on clinically relevant neonatal and maternal biomarkers. The direct biomarkers fatty acid ethyl esters (FAEEs), ethyl glucuronide (EtG), ethyl sulfate, and phosphatidylethanol (PEth) were found to be the most appropriate biomarkers in relation to detection of PAE. To review each biomarker in a clinical context, we have compared the advantages and disadvantages of each biomarker, in relation to its window of detectability, ease of collection, and the ease and cost of analysis of each biomarker. The biomarkers PEth, FAEEs, and EtG were found to be applicable for detection of even low levels of alcohol exposure. Meconium is an accessible matrix for determination of FAEEs and EtG, and blood an accessible matrix for determination of PEth.